Chemosystematic studies of genus oxalis L. in Egypt : Family: Oxalidaceae - Amal Abdelbassir Draz; Eman Mahmoud Shamso; Hasnaa Ahmed Hosni; Sameh Reda Awaad (Cairo : Amal Abdelbassir Draz, 2021)
Five species and one variety belonging to genus Oxalis L. in Egypt were collected and studied from the taxonomic and chemical point of view.The taxonomic part includes the study of morphological, palynological and laminal epidermal characters; these characters were described from both fresh and herbarium specimens.The chemical part includes a detailed study of the chemical profiles of the studied taxa by using different spectrometric and spectroscopic techniques, where GC/MS is used for analysis of volatile and non-polar constituents and LC/QTOF/MS analysis is used for identification of polar compounds. In addition five compounds were isolated and identified from Oxalis pes-caprae.Their structures were elucidated by using chemical as well as spectral tools (acid hydrolysis, UV/vis,1H-NMR and HR-ESI-MS).The obtained results were tabulated to facilitate comparison between the studied taxa based on the criteria extracted from the morphological, palynological, laminal epidermal characters as well as chemical investigations by using the numerical analysis.The relationships between the studied plants were evaluated
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Botany - Microbiology
Issued also as CD
Keywords: Chemosystematic; GC/MS; Oxalis